Phytochemical and Pharmacological Properties of Myristica fragrans Leaves Houtt. - Ariyanti Saputri; Sofa Fajriah; Antonius Herry Cahyana (ALCHEMY Jurnal Penelitian Kimia, 2025)
Myristica fragrans is a widely distributed plant that grows well in Indonesia. This plant, also known as nutmeg, has been used in various fields such as food, aromatherapy, and other industries. Research on nutmeg plants has been widely conducted, but most of it discusses the seeds and mace of nutmeg. However, research on nutmeg leaves is still limited, with only a few studies to be discussed in this review article. This article provides an overview of the chemical compounds, bioactivity, and toxic effects of essential oils and nutmeg leaf extracts collected from the latest literatures (2014–2024). This article aims to draw more attention to nutmeg leaf research to be developed into natural-based medicinal products. Some compounds contained in nutmeg leaves include dihydrokaempferol, myristicin, 1,1,3,3,5,5,7,7,9,9,11,11,13,13-tetradecamethylheptasiloxane, 2,2-dimethyl-1-decanol, bis(2-ethyl hexyl) phthalate, and 9-dodecane-1-al, gamma-terpinene; caryophyllene and others. In addition, nutmeg leaf compounds also have various interesting bioactivities such as antibacterial, antifungal, antioxidant, larvicidal, and good cytotoxic activity. Overall, nutmeg leaves show great potential as a raw material for medicine. The results of this study also show various types of secondary metabolites with interesting bioactivities that require further study.